COMBATING RICE BLAST THROUGH CHEMICALS - SAlKIA, U. N. (Indian Phytopathology, 2002)
Glass house and field experiments conducted during three consecutive rice growing seasons of 1984 and 1985 revealed that out of nine fungicides tested, ediphenphos (hinosan, 0.1 per cent), thiophanate methyl (topsin, 0.1 per cent) and two formulations cif carbendazim (bavistin and agrozim, 0.1 per cent each) could reduce foliar and neck blast to the extent of 73.48-80.81 and 60.47-64.63 per cent respectively with corresponding increase in the yield. Kilex was moderately effective in controlling the disease but was found to be phytotoxic at 0.3 per cent concentration.